Molecular methods and key genes targeted for the detection of fumonisin producing Fusarium verticillioides – An updated review. (December 2019) - Deepa, N.; Sreenivasa, M.Y.
Abstract: Contamination with Fusarium verticillioides not only diminishes the yield and quality of a crop but also produces fumonisin toxin. Fumonisin is a potential carcinogen which is a global concern, since it is a common contaminant of cereals and cereal-based foods. It is associated with a variety of significant adverse health effects in livestock and animals. Molecular based techniques are available for the detection of fumonisin producing F. verticillioides to meet the industry's need for quick results, which cannot be done using conventional mycological methods. Current molecular methods are mainly based on variants of the polymerase chain reaction (PCR) involving gene or species-specific primers, which provide a better approach than traditional methods. The present review discusses advanced molecular methods which are more labor intensive but less time consuming and specifically meant for early detection of fumonisin producing F. verticillioides .